Comment on “Why do women interact with their parents more often than men? The demonstration effect vs. the biological effect” - Oded Stark (The Social Science Journal, 2015)
This Comment takes issue with the inference that Taiwanese data refute the applicability of the demonstration effect in intergenerational transfers. The Comment points to proper and discriminating tests of the demonstration effect.
Keywords: 330; The demonstration effect; Intergenerational transfers; Gender differentiation in care giving